The Comparison of Speech Acts Application by Pascal and Abraham in Youtube Videos - Sena, Banggala Puja; Faridi, Abdurrachman; Yuliasri, Issy (English Education Journal, 2024)
This research examines the use of speech acts in YouTube videos by professional English communication trainers Learning a Language? Speak It Like You’re Playing a Video Game by Marianna Pascal and Think Fast. Talk Smart by Matt Abrahams. It compared speech acts utilized by the two professional trainers to explain how they effectively deliver their messages to diverse audiences. The analysis focused on identifying the realization, similarities, and differences in using Searle’s (1976) five types of speech acts. The data for this research consisted of words, phrases, clauses, or sentences containing speech acts spoken by Pascal and Abraham during their speeches. This research employed a qualitative research method to categorize and analyze the speech acts. The findings revealed the differences in their communication styles despite of the similar predominant use of representative and directive acts. Pascal’s narrative style was appealing and easy to understand compared to Abraham’s logical and authoritative approach. Pascal’s directives inspire self-reflection more, whereas Abraham’s were direct and effective. The research offers a comprehensive perspective on the speech act strategies employed by professional English communication trainers thereby making valuable contributions to speech act theory and its application in real-world contexts.